Estimating Spillover Effect and Leverage Effect Using EGARCH-ARMA Approach in Mongolian Stock Exchange - Lee, Cheng-Wen; Gankhuyag, Dolgion (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2019)
This study checked the spillover effect and leverage effect from 2 January 2012 to 27 December 2017 in the Mongolian Stock Index MSE20 time frame. We found spillover effect on individual stock prices from the market index, but our analysis did not support individual stock has a spillover effect on stock index. In terms of volatility, only market and stock volatility have a bilateral spillover effect. Stock index in particular has a much stronger influence on stock price. Our research did not support previous studies for the leverage effect of the EGARCH-ARMA method, suggesting negative asymmetric influence of volatility such that two financial instruments overlap in their value.